1997
DOI: 10.1053/jhep.1997.v25.pm0008985263
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral abnormalities in patients with cirrhosis detected by proton magnetic resonance spectroscopy and magnetic resonance imaging

Abstract: Hepatic encephalopathy is a common problem in cirrhosis. The pathogenesis of this complication of advanced liver disease still remains unclear. Magnetic resonance spectroscopy was used to assess prospectively cerebral metabolism in 51 patients with histologically proven cirrhosis (Child-Pugh classes A, B, and C, 18, 18, and 15, respectively) and 36 healthy volunteers. According to the results of psychometric tests, overt hepatic encephalopathy, subclinical encephalopathy, and no encephalopathy were found in 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
1
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 45 publications
6
35
1
1
Order By: Relevance
“…13,21 A similar reduction in myoinositol has been reported in adult EHPVO subjects. 4 However, in acute liver failure patients, no significant change in myo-inositol has been observed, indicating that there is insufficient time for osmolytes to compensate for significantly increased glutamine.…”
supporting
confidence: 68%
“…13,21 A similar reduction in myoinositol has been reported in adult EHPVO subjects. 4 However, in acute liver failure patients, no significant change in myo-inositol has been observed, indicating that there is insufficient time for osmolytes to compensate for significantly increased glutamine.…”
supporting
confidence: 68%
“…Our study confirmed previous data showing a decrease of Mi/Cr and Mi/Cho ratios in patients with liver cirrhosis as compared to controls [12][13][14][15][16][17]. In astrocytes myo-inositol acts as an organic osmolyte, and is released from the cells in response to osmotic cell swelling [18].…”
Section: Discussionsupporting
confidence: 91%
“…66 In patients with cirrhosis subjected to ammonia load, this mechanism of osmolar adaptation is clearly reflected in proton MR spectroscopy ( 1 H-MR spectroscopy) studies, which consistently show increases in the glutamine/ glutamate signal intensity accompanied by myo-inositol depletion and decreases in the choline signal intensity (Fig 2). [67][68][69][70][71][72][73] This osmoregulatory mechanism is activated after liver failure and accounts for the protection against massive edema in chronic liver failure. 74 The extent of the 1 H-MR spectroscopy alterations increases with increasing grade of HE, though these changes have also been observed in patients with cirrhosis and neither clinical nor psychometric or neurophysiologic signs of cerebral dysfunction.…”
Section: Ammoniamentioning
confidence: 99%